Application of the Fuzzy Mamdani Method for Predicting Rainfall in the City of Yogyakarta - Rohman, Abdul; Tri Hastono; Andri Prisda Tyaka (Pusat Riset dan Inovasi Nasional, 2024)
Weather and climate play an important role in everyday life, influencing various aspects of society and the environment. The city of Yogyakarta as a cultural center cannot be separated from the impacts of climate change, including rainfall patterns which can have significant effectiveness on daily activities, agriculture and infrastructure. This research uses a fuzzy logic methodology approach with the Mamdani method to predict rainfall. Fuzzy logic has proven to be effective in cold situations and is able to overcome the challenges of missing or incomplete data. The data used in this research was obtained from Bappeda DIY. The implementation for predicting rainfall levels uses Matlab by utilizing the provided Fuzzy Logic Matlab Toolbox. Based on research conducted using a fuzzy logic test to calculate all research accuracy data, an average error value in RMSE was obtained of 39.88%. These results indicate that there is significant error in these predictions, indicating that the fuzzy logic control model is not completely accurate. Therefore, it is necessary to review the data used in this prediction to ensure its accuracy.